Analisis Sifat Mekanik Tarik Komposit Hybrid Matrik Epoxy Serat Rami (Boehmeria Nivea) Dan Serbuk Genteng. - Endar Mukti; Sutrisno; Wahidin Nuriana (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Ramie fiber was chosen for its superior mechanical properties and environmentally friendly characteristics as a renewable material, while roof tile powder was used as an inorganic filler to increase stiffness and utilize abundant construction waste. This study aims to analyze the effect of the composition ratio used on the tensile strength of hybrid composites based on natural ramie fiber (Boehmeria Nivea) and roof tile powder with an epoxy matrix, focusing on mechanical testing, namely tensile testing, to analyze the effect of composite material combinations. The research will be conducted using the hand lay-up method, with variations in the volume fraction of epoxy resin (75%) and ramie fiber (0%; 5%; 10%; 15%; 20%; 25%) and roof tile powder (25%; 20%; 15%; 10%; 5%; 0%). The planned mechanical test include several types of test, including tensile test to analyse the effect of composite material combination.